1990
DOI: 10.1038/bjc.1990.313
|View full text |Cite
|
Sign up to set email alerts
|

4, 6-0-Benzylidene-D-glucopyranose (BG) in the treatment of solid malignant tumours, an extended phase I study

Abstract: Summary 4, 6-0-Benzylidene-D-glucopyranose (BG), a derivative of benzaldehyde (BA), whose anti-tumour action has often been reported, showed responses in 10 out of 24 patients (41.7%). These patients consisted of 11 cases of primary lung cancer, 4 of metastatic lung cancer, 5 of gastric cancer, and one each of cancer of the sigmoid colon, liver, pancreas and prostate. There were two complete responses (one each of ipsilateral lung metastasis from breast cancer and metastatic liver lesions due to gastric cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In the present experiments, no signs of any side-effects were seen in the animals, there was not observed any difference in body weight between drug treated and placebo treated animals (Table I) We know that the drugs tested in clinical studies by Dr Kochi (1980Kochi ( , 1985Kochi ( , 1988, and later by others (Tatsemura et al, 1990), induced some anticancer effect without any observed side-effects and this is given an explanation with the present hypothesis. Warrington (1986) suggested that normal cells, as a response to protein synthesis inhibition, will stop cycling while cancer cells will not.…”
Section: Lack Of Side Effectsmentioning
confidence: 63%
See 1 more Smart Citation
“…In the present experiments, no signs of any side-effects were seen in the animals, there was not observed any difference in body weight between drug treated and placebo treated animals (Table I) We know that the drugs tested in clinical studies by Dr Kochi (1980Kochi ( , 1985Kochi ( , 1988, and later by others (Tatsemura et al, 1990), induced some anticancer effect without any observed side-effects and this is given an explanation with the present hypothesis. Warrington (1986) suggested that normal cells, as a response to protein synthesis inhibition, will stop cycling while cancer cells will not.…”
Section: Lack Of Side Effectsmentioning
confidence: 63%
“…In fact, experiments using various benzaldehyde derivatives against tumours grown in mice have often shown little or no effect, although the same derivatives were reported to be effective in patients (Kochi et al, 1980;1985;1988;Tatsemura, 1990). One can wonder whether this seeming difference between the effect as seen in mice and in humans could be due to some metabolic difference between the two species, or perhaps, to differences in administration of the drug, being i.v.…”
Section: Discussionmentioning
confidence: 85%